The role of switching cost in the e-service recovery framework among banking customers. Issue 1 (14th October 2021) - Jose, Ajay; Mathew, Sonia; G., Rejikumar; Chacko, Dony Peter; Thomas, Ajith K.
Abstract : Purpose: The emergence of tech-driven initiatives in retail banking has created a vast spectrum of system-related service failures; hence, e-service recovery quality is of prime importance to banks to ensure e-service recovery satisfaction. However, e-service satisfaction is dependent on the ease of moving from one service provider to the other; thus, switching costs assume great significance. This study aims to probe the moderating role of switching cost on e-service recovery satisfaction by exploring e-service recovery quality antecedents. Design/methodology/approach: A measurement model is suggested in the contextual settings of the Indian banking scenario and is estimated using structural equation modeling. Responses from 399 e-banking customers, who had experienced a service failure, were sought using a five-point Likert scale. Findings: The result affirms that "recovery expectation" is the most significant predictor of e-service recovery satisfaction, and that switching cost moderates the relation between e-service recovery quality and e-service recovery satisfaction. Practical implications: The study highlights the high relevance of switching costs in the e-banking context and emphasizes investment in marketing strategies and campaigns to do away with switching intentions. It also highlights the relevance of recovery expectations as an antecedent of e-service recovery quality and thus stresses the need to satisfactorily address the same in the e-service recovery process. Originality/value: This study contributes to the e-service recovery satisfaction literature in the banking context by empirically validating the moderating role of switching cost. It also identifies the critical antecedents of banking e-service recovery quality.